What to do when advanced thyroid cancer invades the carotid artery? Therapeutic challenge - Grillo, Vinicius Tadeu Ramos da Silva [UNESP]; Jaldin, Rodrigo Gibin [UNESP]; Bertanha, Matheus [UNESP]; Sobreira, Marcone Lima [UNESP]; Soares, Carlos Segundo Paiva [UNESP]; de Camargo, Paula Angeleli Bueno [UNESP] (FapUNIFESP (SciELO), 2022)
Of all thyroid cancers, anaplastic thyroid carcinoma (ATC) has the lowest incidence and worst prognosis. In this report, we describe a 64-year-old female patient who underwent total thyroidectomy and level VI neck dissection for papillary thyroid carcinoma. During follow-up, she showed signs of regional recurrence and underwent extended neck dissection and cervical esophagectomy. Intraoperatively, there was no cleavage plane between the tumor and the common carotid artery (CCA), so a carotid shunt was implanted and en bloc resection, including the affected CCA and esophagus segments was performed followed by vascular bypass with interposition of a great saphenous vein graft. A pathology review found evidence of anaplastic carcinoma. The patient underwent adjuvant treatment and has no signs of locoregional recurrence. Presented with the possibility of carrying out curative surgery with en bloc resection, the vascular surgeon must be prepared for the surgical options.
O que fazer quando o câncer de tireoide avançado invade a artéria carótida? Desafio terapêutico
Keywords: carotid artery injuries; thyroid neoplasms; vascular surgical procedures; vascular system injuries